Aquisição de pronomes clíticos de português europeu por falantes de chinês: dados sobre a colocação - Gu, Wenjun (Revista da Associação Portuguesa de Linguística, 2019)
This paper presents a pilot-study of a research which aims to investigate the acquisition of the clitic pronouns in European Portuguese (EP) by Chinese learners. Based on an acceptability judgement task, conducted with 20 Chinese students and a control group of 26 native speakers of EP, we would like, on the one hand, to make a better characterization of the development of placement properties of clitic pronouns in Chinese learners’ interlanguage grammars; on the other hand, to contribute to a better understanding of the theoretical proposals on the learnability problems regarding uninterpretable features not available in the first language (L1). Our preliminary results suggest that, as shown in previous works on L1 EP and L2 EP, the conditions which determine proclisis seem to be more difficult to acquire than those for enclisis and the different contexts of proclisis seem to develop gradually, following a similar path to that previously described for L1 EP.